Prevalence of Early Hyperglycemia in Kidney Transplant Recipient in a Tertiary Care Hospitals in Pakistan - Wajeed Gul Bangash, Sher Zaman Khokhar, Aqsa Maqsood, Habib Ur Rehman, Feroze Ahmed Mahar, Aftab Ahmed Channa, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The prevalence of diabetes after renal transplant is higher than before renal transplantation. A significant proportion of transplant patients develop new-onset diabetes (NODAT), which accounts for 30-50% of all deaths in kidney transplant patients and is related with amplified mortality, mainly due to macroangiopathy. This study was conducted to determine the prevalence of early hyperglycemia in kidney transplant recipients for the enhanced pharmacologic management. Study Setting: The current descriptive, cross-sectional study was carried out in the Department of Urology/ Nephrology, Pakistan Institute of Medical Sciences (PIMS), Islamabad and Islam Medical College/ Teaching Hospital, Sialkot. The duration of study was one year from October 2021 to September 2022. Methods: A total of 67 patients who underwent renal transplant during the period in PIMS and at other center within the same vicinity and same protocol of management were enrolled in the study. All patients were followed and fasting blood sugar measurement was performed at bed side on day 5 post-transplantation by FDA and international organization for standardization (ISO) 15197-2003 certified Accu-chek device. Results: A total of 67 patients were enrolled. The mean (± SD) age of patients was 34.5 (± 10.2) years. Out of 67 patients, 48 (72%) patients were males. Out of 67 patients, 19 (28%) patients had positive family history for DM. The mean (± SD) value of fasting blood sugar levels of all the enrolled patients was 129.3 (± 22.4) mg/dL. Out of 67 patients, 41 (61%) were diagnosed to have early hyperglycemia on 5th day after renal transplant. The comparison between the Early hyperglycemic and normoglycemic patients regarding their age, gender, BMI, pre-transplant lipid profile and family history of diabetes showed no statistically significant differences (p>0.05). Conclusion: Study shows that out of 67 patients with post renal transplant, 41 (61%) had early hyperglycemia (fasting blood glucose levels ≥126 mg/dL) during their hospital stay. No statistically significant differences were seen in terms of traditional risk factor for diabetes like age, gender, BMI, lipid profile and family history for diabetes between patients who developed early hyperglycemia and those who did not. Keywords: Renal transplant, hyperglycemia, Adult, end-stage renal disease.